Housing Type and Neighbourhood Safety Behaviour Predicts Self-rated Health, Psychological Well-being and Frequency of Recent Unhealthy Days: A Comparative Cross-sectional Study of the General Population in Sweden. (8th August 2017) - Berglund, Erik; Westerling, Ragnar; Lytsy, Per
Abstract: This study aimed at analysing associations among housing type, neighbourhood safety behaviour, self-rated health (SRH), psychological well-being and unhealthy days in the general population. From 2004 to 2013, 90, 845 Swedes completed a questionnaire about their health, number of days with poor health, psychological well-being, housing type, and whether they refrained from going out based on perception of neighbourhood safety. People not living in private housing and those who did not go out for safety reasons reported lower SRH and psychological well-being and higher frequency of recent unhealthy days and days without work capacity due to poor health.